Ethiopia Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
As part of the US government’s Feed the Future initiative that aims to address global hunger and food security issues in sub-Saharan Africa, the US Agency for International Development is supporting multi-stakeholder agricultural research projects under Africa Research In Sustainable Intensification for the Next Generation (Africa RISING - AR) program. The overall aim of the program is to transform agricultural systems through sustainable intensification projects in Ghana, Ethiopia, Tanzania, Malawi, Mali, and (potentially) Zambia. In Ethiopia, the project, led by the International Livestock Research Institute (ILRI), will be supporting crop-livestock farming systems. Multiple participatory and adaptive agricultural interventions are currently taking place in eight kebeles (Goshe Bado, Gudo Beret, Salka, Ilu-Sanbitu, Jawe, Upper Gana, Emba Hasti and Tsibet) in four regions (Amhara, Oromia, Southern Nations Nationalities and Peoples (SNNP), and Tigray) in Ethiopia, led by researchers from the ILRI. Experts from ILRI have supported or introduced intercropping, new crop varieties, water conservation practices, and integrated tree cropping. The International Food Policy Research Institute (IFPRI) leads the monitoring and evaluation (M&E) activities of the AR program. As part of the M&E activities in Ethiopia, IFPRI contracted BDS Center for Development Research to conduct baseline household and community surveys in Amhara, Oromia, SNNP, and Tigray regions. The main objective of this survey is to collect high-quality baseline household data to support the M&E activities of the AR Program in Ethiopia. More specifically, the survey aims to collect detailed information on the composition of the household, employment, health, agriculture, income and expenditures, credit, assets, subjective welfare and food security, shocks, and the anthropometric status of children and women.